Developing flood hazard maps for the Kelantan floodplain using the HEC-RAS 2D model - See, Too Kay Leng; Mokhtar Jaafar,; Mohd Ridhuan Mohd Jamil,; Risa Novia Wati,; Frankie Marcus Ata, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Since flood disasters bring significant consequences to communities, it is essential to identify effective ways to reduce flood risks. This study aims to develop a flood hazard map for the Kelantan floodplain using a two-dimensional hydraulic modelling technique, integrating HEC-RAS and ArcGIS. Findings indicate that the Kelantan floodplain is highly exposed to severe flood hazards, with a 200-year return period discharge of 17,278.7 m³/s. The results show that high-impact areas will experience severe consequences, such as house demolitions, financial losses, and psychological trauma. This study not only analyses past flood events but also predicts future flood risk zones. The findings are crucial for enhancing community preparedness by providing a comprehensive flood hazard map, which can assist in pre-disaster planning, disaster response, and post-disaster recovery to help sustain community well-being.